Accumulation Differences in Perfluorooctanoic Acid and Its Ether Carboxylic Acid Alternatives in the Manila Clam (Ruditapes philippinarum) - Hanlin QIN; Yujie BI; Shuqi JIANG; Chengchen WU; Zhijun TAN; Qianqian GENG; Mengmeng GUO (Progress in Fishery Sciences)
Perfluorooctanoic acid (PFOA) is a synthetic organic chemical with unique hydrophobic and oleophobic properties. It is extensively used in the production of a wide range of essential industrial and consumer products including aqueous film-forming foams, medical devices, and textiles. PFOA is widespread in aquatic environments and has attracted global attention due to the serious ecological risks it poses. Consequently, several countries and organizations have implemented strict restrictions or controls on its use. In 2019, PFOA and its salts were included as Annex A of the Stockholm Convention on Persistent Organic Pollutants, and in 2023, the Ministry of Ecology and Environment of the People's Republic of China and six other departments issued the "Key Regulated New Pollutant List 2023", which proposed environmental risk control measures for PFOA, its salts, and related compounds. With an increase in regulatory measures, the production and use of PFOA have declined, resulting in the rapid development and use of alternatives. Hexafluoropropylene oxide dimer acid (HFPO-DA), trimer acid (HFPO-TA), and tetramer acid (HFPO-TeA)—composed of CF2 or CF2O repeating units—have emerged as principal alternatives that maintain chemical properties similar to those of PFOA and are predominantly used in the manufacture of fluoropolymers and their processing aids.As filter-feeding organisms, bivalves are prolific and have a broad geographic distribution. They possess a marked capacity for accumulating organic contaminants, making them ideal indicators for monitoring pollution in marine environments and assessing the status of various marine ecosystems. Therefore, Manila clams (Ruditapes philippinarum) were used as the test organism in this study and exposed to two concentrations (2 ng/mL and 200 ng/mL) of PFOA and its alternatives—HFPO-DA, HFPO-TA, HFPO-TeA—within a mariculture setting.The purpose of this study was to analyze the tissue distribution, accumulation, and elimination patterns of these compounds in clams, and to evaluate differences in the accumulation ability of organisms to enrich PFOA and its ether carboxylic acid alternatives in clams by calculating kinetic parameters. Additionally, water-soluble proteins were extracted from the visceral masses and gills of the clams and incubated in vitro to explore the differences in binding rates between the target compounds and clam proteins. The binding modes between the target molecules and proteins were investigated using molecular docking techniques to further elucidate the relationship between molecular and protein interactions and the bioaccumulation properties of clams.It was found that that PFOA and its ether carboxylic acid alternatives were rapidly enriched in Manila clams. The enrichment rate of targets increased as HFPO-DA < PFOA < HFPO-TA < HFPO-TeA, and the enrichment effects in different tissues were visceral mass > gill > mantle > adductor muscle. After a 21-day depuration period, the contaminant levels in Manila clams approached those in the control group. Furthermore, in Manila clams, the accumulation capacity of PFOA and its alternatives, and the binding rates of different target molecules to body proteins were strongly correlated with the target concentrations. Lower target concentrations led to greater absorption rate constants and bioconcentration factors and lower binding rates of the targets to the protein. The target content and protein binding in each tissue were HFPO-DA < PFOA < HFPO-TA < HFPO-TeA. Additionally, the molecular structure of PFOA and its alternatives—particularly the increase in C-O bonds and C-F chains—enhanced their binding affinities with protein residues. The binding forces between PFOA, its alternatives, and the fatty acid-binding protein FABP1-A were further validated by molecular docking studies. The magnitude of the binding energy was HFPO-TeA < HFPO-TA < PFOA < HFPO-DA, and the lower the binding energy, the easier it was to bind to the protein. The polar ends of the targets formed hydrogen bonds with the amino acid residues of FABP1-A, whereas their hydrophobic ends engaged in hydrophobic interactions with nonpolar residues, collectively enhancing the protein binding of PFOA and its alternatives. The number of hydrogen bonds is also an important cause of binding affinity differences in the target proteins.This study elucidates the bioaccumulation behavior of PFOA and its alternatives in bivalves and provides a scientific basis for the control and management of emerging contaminants. Although the levels of PFOA and its alternatives in aquatic environments are currently traceable, the ecological risks associated with their persistence in the environment should not be underestimated. Moreover, the findings on their binding rates to clam proteins offer a scientific basis for the reasonable selection of alternatives. Additionally, the molecular docking data furnish a theoretical basis for investigating the specific binding of PFOA and its alternatives to proteins with different carbon chain lengths and structures.